2017
DOI: 10.1177/1350650116688138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oil starvation on the surface dimple in elastohydrodynamic lubrication contact under opposite sliding conditions

Abstract: Optical interferometry experiments were performed to investigate the dimple phenomena in starved elastohydrodynamic lubrication of point contacts under opposite sliding condition by using a high viscosity polybutene (PB) lubricant. The effects of the bilateral starvation, left starvation, and right starvation on the variation of the oil film under a high slide-to-roll ratio were investigated. It was found that oil starvation could generate a starved constriction, which would make the shape of the oil film rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
(52 reference statements)
1
6
0
Order By: Relevance
“…As shown in Figure 9(i) to 9(k), the film is horizontal and very thin. Figure 9(d) to (h) reveals that the severe grease starvation shrinks the dimple governed by the ''temperature-viscosity wedge'', as reported out by Meng et al 27,32 Around the end of the stroke (Figure 9(k)), there is also no entrapment in the contact.…”
Section: Effect Of Grease Starvationsupporting
confidence: 56%
See 2 more Smart Citations
“…As shown in Figure 9(i) to 9(k), the film is horizontal and very thin. Figure 9(d) to (h) reveals that the severe grease starvation shrinks the dimple governed by the ''temperature-viscosity wedge'', as reported out by Meng et al 27,32 Around the end of the stroke (Figure 9(k)), there is also no entrapment in the contact.…”
Section: Effect Of Grease Starvationsupporting
confidence: 56%
“…As what had pointed out by Zhang et al, 25,26 with the decrease of the surface speed in ZEV condition, the classical big dimple evolved into a small centralized dimple adjoined by regions with very thin film thickness at its both sides. Meng et al 27 pointed out that the effect of lubricant starvation played a similar role as the decrease of the surface speed. The liquidity of grease is poorer than that of the oil, so that the degree of starvation usually increases with the increase of the working cycle.…”
Section: Effect Of Grease Starvationmentioning
confidence: 99%
See 1 more Smart Citation
“…The second issue identified by Ingram et al [4] as potentially affecting the reliability of their test method is the possible existence of an EHL "dimple" during contra-rotation. This effect has been observed specifically under contra-rotation conditions by Guo et al [27,28], Nakahara and Yagi [30] and Meng et al [26] amongst others. Kaneta et al [40] was the first to suggest that, instead of the flat film thickness over the central region of the contact, as predicted and normally measured by the conventional EHL theory, under pure sliding conditions a deep conical thick film region (a dimple) may form within the contact.…”
Section: Potential Effects Of Thermal Wedge In Contra-rotationmentioning
confidence: 61%
“…Ingram et al's method represents an important advance in producing a controlled-condition scuffing test that can be used to explore scuffing mechanisms. However, the authors identified two potential problems: (i) the variability in the obtained results was rather high and (ii) there was uncertainty in the applicability of standard EHD theories to film thickness predictions in contra-rotating contacts under zero or very low entrainment speeds due to a potential formation of a central dimple [26][27][28].…”
Section: Introductionmentioning
confidence: 99%